Impairments of the arm and hand are highly correlated during subacute stroke - Lydia N. Reid; Sean P. Dukelow; Stephen H. Scott (Medical Journals Sweden, 2023)
Background: The classical description of poststroke upper limb impairment follows a proximalto-distal impairment gradient. Previous studies are equivocal on whether the hand is more impaired than the arm. Objective: To compare impairment of the arm and hand during subacute stroke. Method: A total of 73 individuals were evaluated for impairment of the upper limb within 30 days (early subacute) and within 90-150 days (late subacute) of stroke. Impairments were quantified using the Chedoke-McMaster Stroke Assessment (CMSA) for the arm and hand, Purdue Pegboard task, and a robotic Visually Guided Reaching task. Results: In the early phase 42% of participants in the early phase and 59% in the late phase received the same CMSA score for the arm and hand, with 88% and 95% of participants in the early and late phases, respectively, receiving a 1-point difference. Strong correlations exist between the CMSA arm and hand scores (early r = 0.79, late r = 0.75), and moderate - strong correlations exist between CMSA arm and hand scores and Purdue Pegboard and Visually Guided Reaching performances (r = 0.66-0.81). No systematic differences were found between the arm and hand. Conclusion: Impairments in the arm and hand during subacute stroke are highly correlated and do not support the presence of a proximal-to-distal gradient. LAY ABSTRACT Motor impairments are a common occurrence after stroke, and are classically believed to present in a gradient from more impairment in the hand to less impairment in the arm. In this study, participants who had recently had a stroke underwent assessment with the Chedoke-McMaster Stroke Assessment, the Purdue Pegboard task, and a Visually Guided Reaching task to quantify impairment and performance of the arm and hand. Levels of impairment in the arm and hand, as measured with the Chedoke-McMaster Stroke Assessment, were found to be highly correlated. The study also showed strong correlations between quantitative measures of performance for both the arm and hand. Overall, our results do not support the presence of a proximal-to-distal gradient of impairment during subacute stroke.